2010
DOI: 10.3390/molecules15107363
|View full text |Cite
|
Sign up to set email alerts
|

Chemometric Studies on Natural Products as Potential Inhibitors of the NADH Oxidase from Trypanosoma cruzi Using the VolSurf Approach

Abstract: Natural products have widespread biological activities, including inhibition of mitochondrial enzyme systems. Some of these activities, for example cytotoxicity, may be the result of alteration of cellular bioenergetics. Based on previous computer-aided drug design (CADD) studies and considering reported data on structure-activity relationships (SAR), an assumption regarding the mechanism of action of natural products against parasitic infections involves the NADH-oxidase inhibition. In this study, chemometric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 22 publications
0
15
0
1
Order By: Relevance
“…Also, Tasdemir et al () reported the anti‐ T. cruzi activity of chrysin dimethylether ( 153 ; IC 50 : 3.5 μg/ml; SI: 5.51, L6 cells) and 3′‐hydroxydaidzein ( 154 ; IC 50 : 4.7 μg/ml; SI: 4.53, L6 cells; Table ). Scotti, Scotti, Bolzani, and Ferreira () and Scotti, Ferreira, Silva, and Scotti () developed in silico studies to propose a pharmacophore group of many flavonoids and to know about their physicochemical properties, which could influence their biological activities.…”
Section: Natural Flavonoids As Potential Leads For the Treatment Of Mmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, Tasdemir et al () reported the anti‐ T. cruzi activity of chrysin dimethylether ( 153 ; IC 50 : 3.5 μg/ml; SI: 5.51, L6 cells) and 3′‐hydroxydaidzein ( 154 ; IC 50 : 4.7 μg/ml; SI: 4.53, L6 cells; Table ). Scotti, Scotti, Bolzani, and Ferreira () and Scotti, Ferreira, Silva, and Scotti () developed in silico studies to propose a pharmacophore group of many flavonoids and to know about their physicochemical properties, which could influence their biological activities.…”
Section: Natural Flavonoids As Potential Leads For the Treatment Of Mmentioning
confidence: 99%
“…It is actually an oligomeric membrane protein complex that transfers electrons from a relatively low‐potential quinol to a c‐type cytochrome with a high degree of homology (≈85%) of the bc1 subunits (Bohmont, Aaronson, Mann, & Pardini, ). The foremost target enzyme involved is the NADH‐oxidase (Scotti, Ferreira, et al, ).…”
Section: Molecular Targets For the Chemotherapy Of Malaria Leishmanimentioning
confidence: 99%
“…99 Utilizando a base Chemdiv, com 700.000 compostos, a triagem virtual baseada em farmacóforos da cruzaína selecionou 20 compostos, 11 dos quais disponíveis comercialmente. 100 Ensaiados em cruzaína in vitro, alguns dos compostos apresentaram IC 50 102 Os resultados apontam para a relevância do perfil hidrofóbico à atividade biológica estudada.…”
Section: Figura 26 Tio(semicarbazonas) Inibidoras De Cruzaínaunclassified
“…NOX is becoming a potential target for therapeutic interventions in vascular diseases [8]. It was investigated that the action of natural products against parasitic infections involves the NOX inhibition, which therefore may be an underlying mechanism for cytotoxicity in parasites [9].…”
Section: Introductionmentioning
confidence: 99%